(untitled) (k:ON - Kölner Online Journal für Lehrer*innenbildung, 2026)
The Linguistic Risk-Taking Initiative is usually employed in contexts of learning majority languages such as English, French, or German (Cajka, 2021; Cajka et al., 2023; Slavkov &Séror, 2019). This paper, however, pursues a different approach and explores the potential and the implementation of linguistic risk-taking for minoritized languages. It draws on the work of the HORIZON EUROPE project "RISE UP – Revitalising Languages and Safeguarding Cultural Diversity" and reflects on important considerations for adapting the initiative for minoritized language contexts. The theoretical basis for these reflections rests on three main pillars, which are language ecology, new speakers, and a dynamic usage-based approach to language learning. The paper also elaborates on the implementation of linguistic risk-taking in the RISE UP project.